Coconut Palm Waste Product Innovation by Using Eco Friendly Technology - Adi Bejo Suwardi; . Baihaqi; Fazrina Saumi (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2018)
Karya Muda women group was one of the weaving group in Aceh Tamiang District produced various kinds of handicraft. The lack of technology for production equipment and lack of knowledge of natural coloring become an obstacle in developing of their product. The purpose of this activity was produced of weaving product made of stick cesspool from high quality palm oil and market demand by using ATBM and application of natural dyes to product. The activity conducted for five months started from April–August 2017. The method used discussion and active participatory from beneficiaries group by applying adult learning. The result shown that local government of Aceh Tamiang, Paya Bedi Village Government and Karya Muda women group was able to produced various kinds of handicraft production by using palm oil cesspool stick and interested by markets such as women hand bag, tissue box, stationery box, and laptop bag whereas prior that the group were able to produced various kinds of handycraft manually such as plate, broom, vas, and others. On the other hand, the group had been succeed to diversification of products from hand made handycraft to be weaving products.